Microplastic Consumption and Its Effect on Respiration Rate and Motility of Calanus helgolandicus From the Marmara Sea - Isinibilir, Melek; Svetlichny, Leonid; Mykitchak, Taras; Türkeri, Ezgi E.; Eryalçın, Kamil Mert; Doğan, Onur; Can, Gülşah; Yüksel, Esin; Kideys, Ahmet E. (Frontiers in Marine Science, 2020)
Consumption rates of polystyrene microplastics (beads of 6, 12 and 26 μm diameter) and their effects on energy metabolism and motor activity of the copepod Calanus helgolandicus living in the Marmara Sea were investigated. All sizes of microplastic particles were actively consumed and excreted via faecal pellets, however, copepods displayed a significant preference for beads sized 6 μm. In a mixture of algae and microplastics beads of 6 μm, microplastics consumption rates linearly (r2 = 0.78, n = 154) increased 800 times from 50.8 ± 17.3 to 8612 ± 5972 beads ind-1 day-1 with an increase in bead concentration from 10 to 43,000 beads ml-1. The total and basal metabolic rates as well as time spent swimming for C. helgolandicus, decreased 1.7, 1.8 and about 3-fold, respectively after 7-8 days exposure to microplastic treatments, which was similar to the metabolism and activity of starving animals in filtered water. In copepods consuming microplastics, all vital parameters decreased on the first day of exposure, indicating either accelerated starvation, probably due to increased losses of energy and biological matter in the formation of faecal pellets and/or traumatic/toxic effects of the polystyrene beads on the copepods. Our data from laboratory experiments indicate that the presence of large concentrations of microplastics in water, even when mixed with algae, lowered energy metabolism levels of C. helgolandicus.